PEMBINAAN BAGI KELUARGA PENERIMA MANFAAT PROGRAM KELUARGA HARAPAN DAN BANTUAN PANGAN NON TUNAI KAMPUNG PURWOREJO - Ratna Kumala Sari; Farida Juwita; Fajar Sasora (LPPM Universitas Internasional Batam, 2023)
As an effort to accelerate poverty alleviation, since 2007 the Government of Indonesia has implemented PKH. The Family Hope Program (PKH) is a conditional social assistance program for poor families who are designated as PKH beneficiary families. The criteria for PKH beneficiary families are poor families who must meet at least one of the conditions. Based on the survey and interview results, the main problem faced by PKH beneficiary groups in Purworejo Village, Padang Ratu District, was a lack of understanding in accepting the social assistance program. The method used is lecture or coaching. Coaching is the best solution to increase the understanding of beneficiary family members, and can minimize errors in use.